2017
DOI: 10.1103/physrevb.95.054116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local strain heterogeneity on high piezoelectricity in 0.5Ba(Zr0.2Ti0.8)

Abstract: Hz and resonant ultrasound spectroscopy in the frequency range ~0.1-1.2 MHz confirm the existence of three phase transitions with falling temperature, at ~360 K (cubic-tetragonal), ~304 K (tetragonal-orthorhombic) and ~273 K (orthorhombic-rhombohedral). In comparison with BaTiO 3 , however, the transitions are marked by rounded rather than sharp minima in the shear modulus. The pattern of acoustic loss is also quite different from that shown by BaTiO 3 in having a broad interval of high loss at low temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The overall pattern of a wide temperature interval of high loss is thus more typical of loss mechanisms with a wide spread of relaxation times, as seen for example in PbZr 0.53 Ti 0.47 O 3 −Pb(Fe 0.5 Ta 0.5 )O 3 [44], rather than of the single thermally activated process typical of twin-wall motion and freezing, as seen for example in KMnF 3 [45]. Schiemer et al [44] and Zhang et al [6] have attributed this spread to the presence of unit-cell scale-strain heterogeneity and, in the present study, the effect is larger for PIN-PZ-PMN-PT than for PMN-28PT.…”
Section: Elastic and Anelastic Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The overall pattern of a wide temperature interval of high loss is thus more typical of loss mechanisms with a wide spread of relaxation times, as seen for example in PbZr 0.53 Ti 0.47 O 3 −Pb(Fe 0.5 Ta 0.5 )O 3 [44], rather than of the single thermally activated process typical of twin-wall motion and freezing, as seen for example in KMnF 3 [45]. Schiemer et al [44] and Zhang et al [6] have attributed this spread to the presence of unit-cell scale-strain heterogeneity and, in the present study, the effect is larger for PIN-PZ-PMN-PT than for PMN-28PT.…”
Section: Elastic and Anelastic Propertiesmentioning
confidence: 98%
“…These can have similar temperature dependences if the coupling between polarization and macroscopic strain is strong. On the other hand, the examples of PMN [35] and 0.5Ba(Zr 0.2 Ti 0.8 )O 3 −0.5(Ba 0.7 Ca 0.3 )TiO 3 [6] have shown that differences can be revealing of the nature of the relationship between strain and polarization on a local scale. Elastic compliance (1/f 2 ) and permittivity have therefore been plotted on the same graphs for PIN-PZ-PMN-PT and PMN-28PT in Figs.…”
Section: Comparison Of Dielectric and Elastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of high piezoelectricity has been explored based on experimental and theoretical studies, which suggest that perhaps several mechanisms work together to achieve the observed high performance. The following mechanisms have been proposed as origin for high piezoelectricity: flat‐free energy profile at the tricritical point, low polarization anisotropy energy, low energy barrier at the O‐T phase boundary, and large polarization fluctuation in the O phase .…”
Section: Introductionmentioning
confidence: 99%
“…14 Investigations have been taken up world-wide with different aims on the solid solutions of BZT with other materials like: (Ba,Ca)TiO 3 , [15][16][17][18][19] (Bi 1=2 Na 1=2 ÞTiO 3 , [20][21][22][23] 29 NiO, 30 Ni, 31 polyvinyl alcohol, 32 epoxy, 33 Portland cement, 34,35 etc. Further, materials having high dielectric constant (10 3 -10 6 Þ are considered to be important nowadays keeping in view the growing interest in the fields of aeronautic, aerospace, power plants, automotive industries, oil and natural gas industries, various critical components' evaluation in nuclear industries, hybrid or electrically powered vehicles, thermal and geothermal engineering, etc.…”
Section: Introductionmentioning
confidence: 99%